The mechanistical principles and engineering application of roof- cutting for roadway protection in advance of the working face - Zhaotai Li; Yuejin Zhou; Xiaoding Xu; Yuhang Xiao; Yunong Xu (Scientific Reports)
Abstract In coal mining operations, it is often challenging to control the deformation of the roadway in front of the working face. The excessive stress from the surrounding rock of the working face and the difficulties in caving the goaf roof have led to a prominent factor that hinders safe and efficient production in coal mines. For this reason, a mechanical model of the stress field in the advance roadway of the working face is established, and the stress evolution law of the surrounding rock before and after cutting the roof of the roadway is analyzed. Key parameters such as cutting depth, cutting angle, and hole spacing are determined through theoretical calculation, numerical simulation with 3DEC numerical software, and field testing. A kind of roof cutting and pressure relief techniques (TCPAF) for enhanced roadway safeguarding in advance mining face is proposed, and its effectiveness is verified through field testing. The results indicate that the stress on the low-stress side of the leading roadway remains slightly increased, while on the high-stress side, stress decreases significantly, optimizing the stress environment of the surrounding rock. In addition, the research results provide a scientific basis for similar conditions of roadway deformation.